What are the impacts of water deficit, cultivars, and years on the dynamics of nutrient uptake by common bean? Part II: Ca, Mg, and S - Coelho, Anderson Prates [UNESP]; Faria, Rogério Teixeira de [UNESP]; Lemos, Leandro Borges [UNESP]; Filla, Vinícius Augusto [UNESP]; Reis, Maria Albertina Monteiro dos [UNESP] (Taylor & Francis, 2022)
We aimed to explain and compare Ca, Mg, and S uptake dynamics by two common bean cultivars with contrasting growth habits as a function of water deficit severity in two years to generate more specific information for their fertilization management. A field study was set up using the cultivars IAC Imperador, with a determinate growth habit and early cycle, and IPR Campos Gerais, with an indeterminate growth habit and intermediate cycle. These cultivars were maintained under three irrigation levels, that is, severe (54% ETc), moderate (77% ETc), and no water deficit (100% ETc). The absorption order was Ca > Mg > S, regardless of the treatment. For the IAC Imperador, the Ca uptake ranged from 72 to 127 kg ha−1, Mg from 17.2 to 39.1 kg ha−1 and S from 7.9 to 16.5 kg ha−1, while for the IPR Campos Gerais it ranged from 92 to 156 kg ha−1, 21.0 to 36.5 kg ha−1 and 14.6 to 33.7 kg ha−1, respectively. Overall, severe water deficit reduced Ca, Mg, and S absorption by more than 25%. The IPR Campos Gerais presents, on average, 64% higher S accumulation, while the highest Ca and Mg accumulation order depends on the year. Compared to the IAC Imperador, this cultivar showed a later S absorption peak (up to +23 days), and higher interannual variability in the growth and nutrient absorption due to its indeterminate growth habit. These differences evidence the importance of specific fertilizer management practices for Ca, Mg and S in common bean, assisting in optimizing nutrient use.
Keywords: nutrient accumulation; Phaseolus vulgarisL; secondary macronutrients; water regime